The contribution of philanthropic movement for civic education: Lessons learned from generosity amid pandemic - Iqbal Arpannudin; Karim Suryadi; Elly Malihah; Leni Anggraeni (LPMPP Universitas Negeri Yogyakarta, 2023)
The culture of mutual assistance and the generosity of Indonesian citizens significantly grows amid the pandemic. Such culture is an integral part of civic studies as a taste and a practice. The institutionalized mutual aid and generosity practices are part of a philanthropic movement included in the socio-cultural domain of civic studies and civic education. The socio-cultural domain of civic education asserts that civic education is not always construed as a subject in schools. This paper aims to examine the position of philanthropy as part of civic studies and civic education. This study employs grounded theory to investigate philanthropic models in tradition, activities, and movements in building the civic socio-cultural dimension and its contribution to civic education. Data sources in this study were obtained from interviews and analysis of documents related to the philanthropic movement in Indonesia. The data were validated using triangulation of research data sources, and data analysis utilized the constant comparative method with the help of ATLAS.ti version 8. The results show that philanthropy contributes to the domain of academic study of civic education to strengthen and consolidate the science of civic education concerning the tighter relationship during the pandemic between citizens, the government, and the third sector. The contribution for the curricular domain, philanthropy, can be included in teaching materials for civic education learning at schools on materials that discuss citizens and the state.